2018
DOI: 10.1016/j.chemosphere.2017.12.151
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chlorinated organic solvents from hydraulic fracturing wastewater by bare and entrapped nanoscale zero-valent iron

Abstract: With the increasing application of hydraulic fracturing, it is urgent to develop an effective and economically feasible method to treat the large volumes of fracturing wastewater. In this study, bare and entrapped nanoscale zero-valent iron (nZVI) were introduced for the removal of carbon tetrachloride (CT) and 1,1,2-trichloroethane (TCA) in model high-salinity fracturing wastewater. With increasing ionic strength (I) from Day-1 (I = 0.35 M) to Day-90 (I = 4.10 M) wastewaters, bare nZVI presented significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Entrapped nZVI in the alginate polymer matrix showed enhanced removal capacity of 1,1,2trichloroethane (TCA) during the treatment of hydraulic fracturing wastewater (Lei et al, 2018).…”
Section: Nanomaterials Supported On Inert Materials and Polymersmentioning
confidence: 99%
“…Entrapped nZVI in the alginate polymer matrix showed enhanced removal capacity of 1,1,2trichloroethane (TCA) during the treatment of hydraulic fracturing wastewater (Lei et al, 2018).…”
Section: Nanomaterials Supported On Inert Materials and Polymersmentioning
confidence: 99%
“…Before employing nanomaterials in nanoremediation activities, it is important to assess their harmlessness with respect to the environment so that they do not act as pollutants themselves, posing an additional threat to the biota. For example, zero valent iron (nZVI) showed a great potential in the remediation of contaminated water, but it also exerted toxic effects during environmental applications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale zero-valent iron (nZVI) has been widely applied to remove various contaminants from soil and groundwater, for example, chlorinated organics, nitrates, , heavy metals, , and emerging contaminants . Field studies demonstrated that gram per liter or gram per kilogram level of nZVI was needed for efficient remediation. , The extensive application of nZVI particles for water and soil remediation increases their environmental concentration and risk .…”
Section: Introductionmentioning
confidence: 99%